1990
DOI: 10.1002/jsfa.2740520411
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosation of some food‐related tetrahydro‐β‐carboline‐3‐carboxylic acids

Abstract: A number of p-carbolines whose nitroso derivatives are known mutagens and carcinogens are formed in cooked and processed foods. I n this work the formation of N-nitroso derivatives porn 1 -substituted-I,2,3,4-tetrahydro- 9H-p yrido[3,4-b] indole-3-carboxylic acid ( I -R-TH BC-3-COO H ) and nitrite in aqueous solution was studied. The effect of reaction p H , nitrite concentration and duration of the reaction was evaluated. The yield of Nnitroso-1-R-THBC-3-COOH ut 37°C was enhanced ut low pH (about pH 2)and rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In addition, the reversible reaction at indole nitrogen N -9 has been described ( ). According to model reactions ( ), one can expect the presence of N 2 -nitroso-tetrahydro- β -carbolines in nitrite-treated food samples as well as the endogenous formation of such metabolites in the digestive system. Rather surprisingly, tetrahydro- β -carbolines are common food constituents ( 17 and references therein), but only the occurrence of 2-nitroso-tetrahydro- β -carboline-3-carboxylic acid 9 in cured meat products and of 1-methyl-2-nitroso-tetrahydro- β -carboline-3-carboxylic acid 10a/b in soy sauce has been reported ( ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the reversible reaction at indole nitrogen N -9 has been described ( ). According to model reactions ( ), one can expect the presence of N 2 -nitroso-tetrahydro- β -carbolines in nitrite-treated food samples as well as the endogenous formation of such metabolites in the digestive system. Rather surprisingly, tetrahydro- β -carbolines are common food constituents ( 17 and references therein), but only the occurrence of 2-nitroso-tetrahydro- β -carboline-3-carboxylic acid 9 in cured meat products and of 1-methyl-2-nitroso-tetrahydro- β -carboline-3-carboxylic acid 10a/b in soy sauce has been reported ( ).…”
Section: Introductionmentioning
confidence: 99%
“…THβC could react with nitrite already in foods, the mouth, or the stomach, giving rise to mutagenic compounds. Salvi and Choughuley (1990) and Sen et al (1991Sen et al ( , 1995 reported the nitrosation of some foodrelated THβC-3-COOHs.…”
Section: Introductionmentioning
confidence: 99%
“…Tetrahydro-ßcarbolines can react with nitrite already in foods, in the mouth, or in the stomach, giving rise to mutagenic compounds. Salvi and Choughuley (1990) reported the nitrosation of some food-related tetrahydro-/3-carboline-3-carboxylic acids.…”
Section: Introductionmentioning
confidence: 99%